Strategi Guru PAI dalam Pencegahan Radikalisme Digital melalui Moderasi Beragama di Al-Manar Medan Johor - Arif Syahputra; Abd Rahman (Journal of Islamic Education Students (JIES), 2026)
The development of digital media has significantly influenced how students access and understand religious teachings. While digital media expands access to religious literacy, it also poses risks related to the spread of exclusive and radical religious ideologies. This study aims to analyze religious moderation education as a strategy of Islamic Religious Education (PAI) teachers in preventing digital radicalism at Al Manar Private Islamic Senior High School, Medan Johor. This research employs a qualitative descriptive approach using interviews, observations, and documentation. The informants include the principal, PAI teachers, and students. The findings indicate that religious moderation education is implemented through the integration of wasathiyah values in PAI learning, teacher role modeling, strengthening digital religious literacy, and fostering tolerant school culture. Religious moderation education functions as a preventive strategy to develop students’ critical, moderate, and inclusive attitudes, thereby minimizing exposure to digital radicalism. The study confirms the strategic role of PAI teachers as agents of moderation in responding to the challenges of radicalism in the digital era.